Analisis faktor-faktor yang mempengaruhi konsumsi daging ayam petelur afkir di Kecamatan Selupu Rejang, Bengkulu - Muninggar, Restu Mekar; Hakim, Muhammad (Jurnal Sain Peternakan Indonesia, 2025)
This study aims to examine the community’s decision-making process for purchasing culled layer chicken meat and to identify the factors that affect its consumption in the Selupu Rejang Subdistrict. The research was conducted from April to June 2024 in Talang Lahat, Baru Palbatu, Simpang Nangka, and Karang Jaya Urban Villages. The sample comprised 60 respondents, selected through purposive sampling based on the criterion of consuming culled layer chicken meat. The analysis of factors affecting the consumption of purchasing culled layer chicken meat employed multiple linear regression.  The results show an Adjusted R² of 0.639, indicating that the independent variables explain 63.9 percent of the variance in culled layer chicken meat consumption. Simultaneously, the independent variables significantly influence the consumption. The independent variables with a significant effect are family size, education level, and broiler chicken meat price. Family size and education level have substantial adverse effects (P < 0.05), whereas broiler chicken price has a significant positive impact (P < 0.05) on consumption of culled layer chicken meat. The decision-making process in consuming culled layer chicken meat includes need recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior.